2008
DOI: 10.2341/07-115
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of Compromised Bonding in Bleached Enamel Using Antioxidant Gel

Abstract: Dental bond strength is significantly reduced when bonding is performed immediately after bleaching treatments. It has also been reported that the application of an antioxidant after bleaching treatment improves the adhesive bond strength of oxidized enamel tissue. The application of an antioxidant in gel form by the patient makes the application process easier and shortens time spent in the clinic. SUMMARYMany studies have shown a considerable reduction in the enamel bond strength of resin composite restorati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
80
2
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(99 citation statements)
references
References 24 publications
(37 reference statements)
7
80
2
6
Order By: Relevance
“…Management of these discolorations can be done conventionally, by using a veneer/crown or more conservatively by bleaching. [1][2][3] Various concentrations of peroxide are being used as whitening systems to bleach enamel. Hydrogen peroxide because of its low molecular weight diffuses through enamel, decomposes into oxygen and perhydroxyl free radicals.…”
Section: Introductionmentioning
confidence: 99%
“…Management of these discolorations can be done conventionally, by using a veneer/crown or more conservatively by bleaching. [1][2][3] Various concentrations of peroxide are being used as whitening systems to bleach enamel. Hydrogen peroxide because of its low molecular weight diffuses through enamel, decomposes into oxygen and perhydroxyl free radicals.…”
Section: Introductionmentioning
confidence: 99%
“…Bleaching studies that compared different Asian ethnic groups (e.g., Chinese, Koreans, Japanese, and Malays) will be more relevant as dissimilarities arising from genetic alternations and environmental influences are anticipated. A two-fold increase in ΔE* (3.23-6.35) was observed in canines immediately after the first treatment and 1 week after OB; this phenomenon may be explained by remnant perhydroxyl radicals in the tooth structure arising from the high concentrations of bleaching agent used (31,32).…”
Section: Discussionmentioning
confidence: 98%
“…The additives within hydrogel may reduce the efficacy of the material, thus decreasing the ascorbate diffusivity [10,14,28]. Conversely, it was reported that when chemical substances of SA are converted into hydrogel form, their drug releases rates are much slower than in the solution form, and their efficiency periods could be much longer [12]. Moreover, the application of SA solution is more difficult because its flowability and should be applied several times prior to bonding [10,17].…”
Section: Sodium Ascorbate Presentationmentioning
confidence: 99%
“…Most studies, which tested the effectiveness of AS in reversing compromised bond strengths, used carbamide peroxide at low concentrations [5,[7][8][9][10][11][12][13][14][15][16]20,21,25,[28][29][30]33]. It is possible that SA was more effective in teeth bleached with carbamide peroxide due the hydrogen peroxide releases a high oxygen concentration [37].…”
Section: Sodium Ascorbate Versus Bleaching Agent Typementioning
confidence: 99%
See 1 more Smart Citation